Dedicated business models: Connecting firms' values with the systemic requirements of sustainability - Sophie Urmetzer (Journal of Business Models (JOBM), 2021)
Purpose: The concept of dedicated business models is drafted to bridge the gap between the micro-level value frameworks of individual firms and the macro-level systemic requirements of sustainability transformations. Design: Three theoretical concepts are drawn on to describe the potential relations between firms' strategies and the normative orientation of economic systems: Dedicated innovation systems to represent the macro-level and their innovation paradigms as the connection to the micro-level which is represented by business models employed by the individual firms. Then, the scientific literature is reviewed systematically and three propositions are developed that conceptualize dedicated business models. Findings: Business models that contribute to an increased dedication to sustainability in innovation systems take effect on the paradigmatic level and can be expected to feature: (i) an explicit commitment to sustainability-related values; (ii) the active creation and exploitation of new networks to gain access to untapped material, technological, intellectual, and institutional resources that promise higher levels of sustainability; and (iii) mechanisms to nurture and reinforce changed demands of consumers and suppliers in terms of sustainability principles. Limitations: The paucity of relevant literature limits the substantiation of the theoretical argument. It also lacks an empirical verification, which is beyond the scope of this conceptual paper. Originality: The study contributes to the growing scholarship on business models by highlighting their potential effect on innovation paradigms.
Keywords: 650; Sustainable business model; dedicated business model; innovation system; dedicated innovation system; innovation paradigm; sustainability transformation